Abdominoscrotal Hydrocele with Intestinal Malrotation: A Rare Association. (8th August 2012) - Jain, Sonal; Singh, Ragini; Singh, Surendra Kumar; Singh, Vikram; Shantanu, Kumar
Abstract : Abdominoscrotal hydrocele is an uncommon clinical entity and so is intestinal malrotation. We report a case of 15 year old boy who presented with lump in abdomen previously diagnosed as mesenteric cyst on ultrasound. A multislice CT scan and repeat ultrasound not only diagnosed the case as abdominoscrotal hydrocele but also detected intestinal malrotation with positive whirl sign. This is the first reported case of abdominoscrotal hydrocele with intestinal malrotation.